Clinical Characteristics and Risk Factors Assessment of Ischemic Stroke Patients in a Tertiary Care Hospital in Nepal - Sahani, Bikash; Shrestha, Bhakta Dev; Lama, Ganesh; Yadav, Shree Narayan; Amatya, Prasanna Bahadur (Med Phoenix, 2024)
Introduction: Stroke is a major global health burden in society causing mortality and disability after ischemic heart disease. It can be prevented by modification of major risk factors like hypertension, smoking, diabetes, alcoholism, dyslipidemia, and atrial fibrillation. This study intended to measure the clinical characteristics and the risk factors associated with ischemic stroke in patients admitted to NAMS Bir Hospital, Kathmandu, Nepal. Materials and Methods: This study was a hospital-based cross-sectional observational study conducted at NAMS Bir Hospital from November 2019 to June 2020. Data was collected from all the patients presented with stroke and the data was analyzed with SPSS version 26. Results: Out of the 92 patients presented with stroke, ischemic stroke was seen in 70(76%), and hemorrhagic stroke was seen in 22(24%) of the patients. In the study 39(65%) were Male and 21(35%) were Female with a mean age of 65.57 years ± 14.88 years. Weakness of the limb (87%) and deviation of the angle of the mouth (60%) were the presenting symptoms in most of the cases. Middle cerebral artery territory (51%) was the most common site of lesion involved in ischemic stroke. Hypertension and Smoking were seen in 70% and 61% of cases and were the most common factors associated with ischemic stroke followed by alcohol consumption and dyslipidemia. Conclusion: Ischemic Stroke was more common than hemorrhagic stroke among all the cases admitted to the hospital. It was predominant in older male age groups. Hypertension and Cigarette Smoking were the most common risk factors associated with Ischemic Stroke.